Peran Bimbingan Konseling dalam Menanggulangi Kasus Bullying Verbal di SMP - Putri, Rossalina Eka; Marcela, Utari; Ain, Wulan Fatha Kuri; Maradon, Permai Dwiki; Shobabiya, Mahasri (TSAQOFAH, 2024)
Bullying in general is often found in any sphere. Bullying is the act of using power to hurt a person or group of people verbally, physically or psychologically so that the victim feels depressed, traumatized and helpless (Sejiwa, 2008). This research uses qualitative research with a descriptive approach. Researchers conducted direct interviews, direct observation and also used document study methods to strengthen and stabilize the various data obtained. Efforts that have been made by schools and BK teachers to deal with the problem of bullying are by providing understanding, materials and also activities or actions to avoid bullying to all students, of course this can reduce, stop and prevent bullying, especially verbal bullying. Teachers as school environment educators must have techniques, strategies and efforts to overcome cases of bullying in schools. Guidance and Counseling teachers must be able to prevent bullying behavior by always instilling good moral values in students, providing personal services to perpetrators and victims, and providing frequent and intense guidance services.